Overview of Brain Microdialysis - Vladimir I. Chefer; Alexis C. Thompson; Agustin Zapata; Toni S. Shippenberg (2009)
The technique of microdialysis enables sampling and collecting of small-molecular-weight substances from the interstitial space. It is a widely used method in neuroscience and is one of the few techniques available that permits quantification of neurotransmitters, peptides, and hormones in the behaving animal. More recently, it has been used in tissue preparations for quantification of neurotransmitter release. This unit provides a brief review of the history of microdialysis and its general application in the neurosciences. The authors review the theoretical principles underlying the microdialysis process, methods available for estimating extracellular concentration from dialysis samples (i.e., relative recovery), the various factors that affect the estimate of in vivo relative recovery, and the importance of determining in vivo relative recovery to data interpretation. Several areas of special note, including impact of tissue trauma on the interpretation of microdialysis results, are discussed. Step-by-step instructions for the planning and execution of conventional and quantitative microdialysis experiments are provided.